2009
DOI: 10.1017/s0007114508162110
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroxylated phenolic acids derived from microbial metabolism reduce lipopolysaccharide-stimulated cytokine secretion by human peripheral blood mononuclear cells

Abstract: Oligomers and polymers of flavan-3-ols (proanthocyanidins) are very abundant in the Mediterranean diet, but are poorly absorbed. However, when these polyphenols reach the colon, they are metabolised by the intestinal microbiota into various phenolic acids, including phenylpropionic, phenylacetic and benzoic acid derivatives. Since the biological properties of these metabolites are not completely known, in the present study, we investigated the effect of the following microbial phenolic metabolites: 3,4-dihydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(91 citation statements)
references
References 36 publications
(45 reference statements)
1
88
0
2
Order By: Relevance
“…The bioactivity of specific phenolic acids is less well defined, with examples including 3,4diOHPAA an inhibitor of enzymes involved in detoxification (GSTT2), inflammation (COX-2) and anti-proliferative activity in HCT-116 colon cancer cells [67,70]; 3,4-diOHPPA (3 µM) and 3,4-diOHPAA (3 µM), inhibitors of the pro-inflammatory cytokines such as TNF-a, IL-1b and IL-6 in lipopolysaccharide-stimulated peripheral blood mononuclear cells [70,71]; and gallic acid (882 µM) inhibitor of Clostridium histolyticum in in vitro faecal fermentation [65,72].…”
Section: Discussionmentioning
confidence: 99%
“…The bioactivity of specific phenolic acids is less well defined, with examples including 3,4diOHPAA an inhibitor of enzymes involved in detoxification (GSTT2), inflammation (COX-2) and anti-proliferative activity in HCT-116 colon cancer cells [67,70]; 3,4-diOHPPA (3 µM) and 3,4-diOHPAA (3 µM), inhibitors of the pro-inflammatory cytokines such as TNF-a, IL-1b and IL-6 in lipopolysaccharide-stimulated peripheral blood mononuclear cells [70,71]; and gallic acid (882 µM) inhibitor of Clostridium histolyticum in in vitro faecal fermentation [65,72].…”
Section: Discussionmentioning
confidence: 99%
“…In a bottomup approach, potential bioactivity of gut microbiota-mediated metabolites needs to be screened in relevant in vitro and animal models. In a recent screening exercise, gut-microbial polyphenol metabolites were indeed able to reduce the ex vivo response of peripheral blood mononuclear cells to an inflammatory challenge (108). When screening gut-mediated metabolites for biological activity, one should however take into account the different conjugation routes once they have entered systemic circulation (109).…”
Section: Bioavailability-bioactivity Relationsmentioning
confidence: 99%
“…, TNF-α, IL-1β and IL-6, in LPS-stimulated PBMC [225]. The phenolic acids used were at a biological concentration level (1 mM) within the range (0.1–10 mM) found in plasma samples after cocoa polyphenol intake [227].…”
Section: Cocoa Polyphenols and Cvd Inflammatory Markersmentioning
confidence: 99%
“…The concentrations of IL-6 were reduced with 3,4-DHPPA and 3,4-DHPAA pretreatment. This study demonstrated that dihydroxylated phenolic acids derived from colonic microbial metabolites could probably act as an anti-inflammatory agent, providing favourable effects on CVD [225]. …”
Section: Cocoa Polyphenols and Cvd Inflammatory Markersmentioning
confidence: 99%